The effects of five weeks of high-intensity interval training on perceptual and lactate responses in female futsal players: A comparison between the two models - Dittrich, N.; Arins, F. B.; Teixeira, A. S.; Carminatti, J. L.; de Lucas, R. D.; Guglielmo, L. G. A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The purpose of this study was to compare the effects of two models of high-intensity interval training (HIIT) performed over five weeks, on the perceptual and blood lactate responses in elite futsal players. Methods: Sixteen female futsal players (divided in two groups) performed the Futsal Intermittent Endurance Test (FIET) to determine the peak velocity (PVFIET). Both training models (twice a week during five weeks totaling 10 sessions) were designed from shuttle running intervals and consisted of four sets of 4-minute bouts with 3-minutes of rest intervals between the sets. The difference between the two models was the intermittence timing in each set, one being performed by 7.5s of running and 7.5s of resting (HIIT7.5x7.5), and the other by 15s of running and 15s of resting (HIIT15x15). The intensity used for the HIT7.5x7.5 was ~ 88 %PVFIET and for the HIT15x15 was ~ 85 %PVFIET. The blood lactate concentration [La] following each set and a session rating of perceived exertion (RPE) were assessed during the second and tenth training sessions. Results: There were no "training model x time" interactions and main effect for the training model (p>0.05) regarding the RPE score. However, significant main effect findings were found for time (F=25.52, p< 0.001) showing that RPE score was reduced from 2nd to 10th training sessions (HIIT7.5x7.5 = 4.3 ± 0.8 vs. 2.4 ± 1.1 au; HIIT15x15 = 4.1 ± 0.4 vs. 2.9 ± 0.6 au, respectively). The ANOVA results also indicated a non significant three-way interaction effect (p>0.05) for lactate responses. However, a significant "time x sets" interaction (F=12.25, p=0.002) was found for lactate responses. After the training period, the blood [La] following each set was similarly reduced in both HIIT7.5x7.5 and HIIT15x15 groups. Thus, the progressive increase in the blood [La] over the 4 sets shown in the 2nd session was not observed in the 10th session, displaying a steady-state pattern between the sets. Discussion: The present study compared the two models of HIIT performed in shuttle running derived from FIET. The main hypothesis was that the model with more changes of direction (i.e. HITT15x15) could trigger greater improvements in perceptual and lactate responses. In conclusion, the completion of the 10 training sessions in both HIIT models may elicit similar improvements in perceptual and lactate responses in female futsal athletes.